2017
DOI: 10.1007/s00428-017-2065-7
|View full text |Cite
|
Sign up to set email alerts
|

Breast carcinoma subtypes show different patterns of metastatic behavior

Abstract: The aim of our retrospective study was to analyze patterns of subtype specific metastatic spread and to identify the time course of distant metastases. A consecutive series of 490 patients with breast cancer who underwent surgery and postoperative treatment at Semmelweis University, Hungary, and diagnosed between the years 2000 and 2007 was identified from the archives of the 2nd Department of Pathology, Hungary. Molecular subtypes were defined based on the 2011 St. Gallen recommendations. Statistical analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
64
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 69 publications
(72 citation statements)
references
References 44 publications
6
64
0
2
Order By: Relevance
“…The close link between these subtypes and different clinical behaviors of breast cancers as well as its different response to therapeutic chemotherapy regimens has also been identified (1,2). It is, thus, suggested a significant association between these molecular subtypes and known risk factors for breast cancer through different etiological pathways (3,4).…”
Section: Introductionmentioning
confidence: 91%
“…The close link between these subtypes and different clinical behaviors of breast cancers as well as its different response to therapeutic chemotherapy regimens has also been identified (1,2). It is, thus, suggested a significant association between these molecular subtypes and known risk factors for breast cancer through different etiological pathways (3,4).…”
Section: Introductionmentioning
confidence: 91%
“…One of these factors is the breast cancer metastasis molecular subtype, based on the estrogen/progesterone receptor and the HER2 receptor amplification status. Recently, Molnár et al [31] showed that in case of recurrence, the best OS is associated with positive hormone receptor [HoR and negative human epidermal growth factor receptor 2 (HER2)] status of tumors (luminal A), followed by luminal B1 and B2 subtypes, defined as HoR+/HER2- with a Ki67 labeling index (LI) > 15% and HoR+/HER2+, respectively. Significant shorter OS was seen in patients with HoR-/HER2+ enhanced and HoR–/HER2– (triple negative cancer; TN) tumor subtypes [31].…”
Section: Characteristics Of Metastatic and Recurrent Breast Cancermentioning
confidence: 99%
“…Recently, Molnár et al [31] showed that in case of recurrence, the best OS is associated with positive hormone receptor [HoR and negative human epidermal growth factor receptor 2 (HER2)] status of tumors (luminal A), followed by luminal B1 and B2 subtypes, defined as HoR+/HER2- with a Ki67 labeling index (LI) > 15% and HoR+/HER2+, respectively. Significant shorter OS was seen in patients with HoR-/HER2+ enhanced and HoR–/HER2– (triple negative cancer; TN) tumor subtypes [31]. Additional prognostic factors regarding the OS of distant relapse are: (a) the time-point of relapse [8], (b) the localization of recurrent disease, and (c) the metastasis load at the time of diagnosis.…”
Section: Characteristics Of Metastatic and Recurrent Breast Cancermentioning
confidence: 99%
See 2 more Smart Citations